FRI0030 Jak2/stat3 is a major pathway of leptin-induced interleukin-6 production by rheumatoid synovial fibroblasts. (23rd January 2014) - Muraoka, S.; Kusunoki, N.; Shikano, K.; Kaburaki, M.; Kitahara, K.; Tanaka, N.; Kaneko, K.; Yamamoto, T.; Kusunoki, Y.; Takagi, K.; Hasunuma, T.; Endo, H.; et al.
Abstract : Background: Since proinflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6, play major pathophysiological roles in rheumatoid arthritis (RA), their inhibitors have recently been developed as potent biological anti-rheumatic drugs. However, they are not curative and the effects are still partial, with many patients failing to respond. Leptin is the product of the ob gene, and is a peptide hormone synthesized almost exclusively by adipocytes that regulates appetite and energy expenditure. It is also suggested that leptin may contribute to inflammation and autoimmunity. We previously reported that serum leptin level was elevated in patients with RA [1 ]. Accordingly, we examined the direct effects of leptin on cultured rheumatoid synovial fibroblasts (RSFs) in the present study. Objectives: To determine the effects of leptin on the production of proinflammatory cytokines by RSFs. Methods: Synovial tissue was obtained at total knee replacement operation from patients with RA who gave consent. RSFs were harvested from the synovial tissues of these patients. Leptin receptor mRNAs were detected by reverse transcription–polymerase chain reaction. Productions of mRNA by RSFs and protein concentrations of TNF-α, IL-1β, and IL-6 in the culture medium were detected by real-time PCR and ELISA kit, respectively. Small interfering RNA (siRNA) was transfected into RSFs to down-regulate the expression of leptin receptor. Effects of inhibitors of janus kinase 2 (JAK2), phosphatidylinositol 3-kinase (PI3K), and mitogen-activated protein kinase (MAPK) on IL-6 production were evaluated. Phosphorylation of signal transducer and activator of transcription 3 (STAT3) in RSFs were determined by Western blot analysis. This study was approved (No. 19021) by Ethics Committee of Toho University School of Medicine. Results: We detected leptin receptor mRNAs in RSFs. Expressions of IL-1β and IL-6 mRNAs were enhanced in a concentration-dependent manner by addition of leptin to RSFs. IL-6 secretion by RSFs showed an increase after leptin stimulation, while IL-1β did not increase in the culture media. Leptin-induced production of IL-6 by RSFs was decreased after exposure to siRNA targeting leptin receptor (Ob-Rb). A JAK2 inhibitor, but not PI3K and MAPK inhibitors, decreased leptin-induced IL-6 production. Enhanced phosphorylation of STAT3 was observed in RSFs after stimulation by leptin. Conclusions: Leptin possibly acts as a proinflammatory cytokine that up-regulates IL-6 production in RSFs via activation of JAK2/STAT3 in RSFs. Leptin and JAK/STAT pathway may represent a new alternative therapeutic target in the treatment of RA. References: Yoshino T, Kusunoki N, Tanaka N, Kaneko K, Kusunoki Y, Endo H, Hasunuma T, Kawai S. Elevated serum levels of resistin, leptin, and adiponectin are associated with C-reactive protein and also other clinical conditions in rheumatoid arthritis. Intern Med. 2011;50:269. Disclosure of Interest: None Declared